Shared-learning experience during a clinical pharmacy practice experience - Zakaria, Syahiera Farhana; Awaisu, Ahmed (American Association of Colleges of Pharmacy (AACP), 2011)
Objective. To implement a shared learning approach through fourth-year students’ mentorship of third-year students and to assess the perceptions of the mentored students on the value of their shared learning experience.